Managerial Strategy of Dasan Lekong Community Health Center, East Lombok to Improve Utilization of Electronic Medical Records by Medical Personnel - Rangga Kembang Taruna; Purwadhi Purwadhi; Ign. Wiseto P. Agung (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The digital transformation in the healthcare sector encourages the implementation of Electronic Medical Records (EMR) to improve service quality and the efficiency of patient data management. However, the implementation of EMR at Dasan Lekong Community Health Center (Puskesmas) still faces various technical and managerial challenges. This study aims to identify problems, analyze causal factors, determine priority issues to be addressed, and formulate managerial strategies for EMR development. This research employs a qualitative descriptive method with a case study approach. Data were collected through interviews and direct observations involving eight participants directly engaged in EMR management. Data analysis was conducted using four analytical tools: the HOT-Fit Model to identify Human, Organization, and Technology factors; the Fishbone Diagram to determine root causes; the USG (Urgency, Seriousness, Growth) Method to prioritize issues; and SWOT Analysis to develop managerial strategies. The findings reveal that the main obstacles to EMR implementation include limited infrastructure (computers, servers, and network), frequent system errors or slowdowns, inadequate staff skills, and unclear standard operating procedures (SOPs) with insufficient managerial support. Based on the USG analysis, technology and infrastructure are identified as top priorities, followed by human resource competence enhancement and organizational policy improvement. Recommended strategies include upgrading technological facilities, conducting continuous training, establishing standardized SOPs, and strengthening leadership support.